Augmenting NOx reduction in diesel exhaust by combined plasma/ozone injection technique: a laboratory investigation. Issue 1 (1st March 2018) - Madhukar, Apeksha; Rajanikanth, Bangalore S.
Abstract : With the advent of non‐thermal plasma technique for diesel exhaust treatment attention is being focused on reducing oxides of nitrogen (NO x ) both from stationary as well as automobile sources. In this work, an attempt has been made to enhance NO x reduction only by utilising a plasma/ozone injection approach without resorting to additional treatments based on catalysts/adsorbents. It was observed that cascading ozone injection with discharge plasma enhances the reduction of NO x as high as 95% for the specific energy of 123 J/l. In the long run, this plasma‐only based approach may be beneficial or a possible alternative for catalyst/adsorbent based NO x treatments. The results have been discussed and a comparative analysis has been made with respect to individual plasma and ozone injection treatment.